Partial climatic risk screening, adaptation and livelihoods in a coastal urban area in Ghana - Dovie, D.B.K.; Pabi, O. (Habitat International, 2023)
Coastal urban areas worldwide are increasingly becoming convergence points for climatic hazards, demographic shifts, and spatial development. However, the presence of societal demands that impact both livelihoods and urban planning in response to climatic hazards undermines the potential positive outcomes. This research, conducted in a coastal urban area of Ghana’s Greater Accra Region, utilized the Community-based Risk Screening Tool – Adaptation and Livelihoods (CRiSTAL) developed by the International Institute for Sustainable Devel opment (IISD) to analyze the experiences of climatic hazards and overall livelihoods of the population. The study employed Ghana’s Census Sampling Frame for implementation, and Participatory Learning Approaches, to collect data which it identified floods, heavy storms, and heat stress as the most significant hazards. These hazards greatly influenced the population’s physical, social, and financial livelihood assets, resulting in losses and damages caused by heavy rains, storms, and subsequent floods. Extreme heat also had a notable impact on human and financial resources. The local population prioritized human mobility and livelihood diversification as important adaptation strategies. The findings have important policy implications, highlighting the need to address barriers and disruptions in resilience-building and sustainability efforts, emphasizing the significance of prioritizing policy investment and considering climate change uncertainties in planning towards minimizing “urban climate policy inhibition” (Urban-CPI). The study also revealed valuable lessons, such as CRiSTAL’s ability to bridge the gap between climatic risk and livelihood issues, bringing them closer to communities and enhancing preparedness to adapt to climatic risks and impacts on livelihoods
Research Article
Keywords: Floods; Heat stress; Human mobility